STRATEGI PEMERINTAH DESA DALAM UPAYA PEMANFAATAN KAIN TENUN SASAK SEBAGAI BRANDING IMAGE DI DESA SADE - Lalu Putrwandi Karjaya; Nune Ganggas Eka Arowana; Muhammad Fahier Fabian; Suliza Nurbayani Karniala; Zikry Aulia Ghifary Fajar (Media Bina Ilmiah, 2024)
The development of tourism in Indonesia has led to the emergence of various types of tourism, one of which is tourism based on the customs and culture of a region. One of the traditional tourist areas that can be found in Indonesia is the Dese Sade traditional cultural tourist village which is located on the island of Lombok. The Dese Sade traditional cultural tourism offers various types of commodities and one of them is the typical Dese Sade sasak woven cloth commodity. This commodity is quite popular among local and international communities, so it has the potential to be used as a branding image for the Dese Sade traditional cultural tourist village itself.Empowerment of the typical Dese Sade sasak woven cloth commodity has considerable potential as a branding image in the area. In this era of modernization, many people are interested in the traditional cultures of a region which can then be used as souvenirs or souvenirs when they visit and have the opportunity to learn more about the customs and culture that exist in an area. Therefore, Dese Sade traditional cultural tourism offers these commodities as a way of promotion in branding their own traditional and cultural village tourism.In writing this research, the author tried to examine in more depth the empowerment of the typical Dese Sade sasak woven cloth as a commodity in terms of branding the area's image. The author uses the theory/concept of branding image to find out more deeply about the empowerment efforts carried out by the village government (traditional leaders) in utilizing the typical Dese Sade sasak woven cloth commodity. Then the method used in this writing is descriptive qualitative to provide a clear picture of the efforts made by the village government in branding its traditional tourism villages in a specific and structured manner